The Impact of Abortion Legalization on Fertility and Maternal Mortality: New Evidence from Mexico - Damian Clarke; Hanna Muehlrad (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2016)
We examine the effect of a large-scale, free, elective abortion program implemented in Mexico City in 2007. Prior to this program, all states and districts in Mexico had very limited, or no, access to elective abortion. A localized reform in Mexico City resulted in a sharp increase in the request and use of early term elective abortions: approximately 90,000 abortions were administered by public health providers in the four years following the reform, versus only 62 in the five years preceding the reform. We provide evidence using national vital statistics data from Mexico covering over 23 million births and over 11,000 cases of maternal deaths. Our difference-in-difference estimates suggest that this program resulted in a reduction in births by 2.3 to 3.8% among women aged 15-44 and by 5.1 to 7.1% among teenage women (15-19 year-olds). Similar results are found for maternal mortality, for which we find a sharp fall in the rate of maternal deaths, by 8.8 to 16.2% for women aged 15-44 and by 14.9 to as much as 30.3% among teenagers. All told, the reform appears to increase the average age of women at first birth, and reduce the number of mothers giving birth at higher parities.
Keywords: J13; I15; I18; O15; 330